1998
DOI: 10.2105/ajph.88.3.481
|View full text |Cite
|
Sign up to set email alerts
|

The effect of lead exposure on behavior problems in preschool children.

Abstract: OBJECTIVES: Interpreting associations between lead exposure and child behavior problems is difficult because studies have not controlled for sociodemographic confounders or have used shed teeth to mark exposure. This study explored associations between blood lead and preschool behavior. METHODS: Children from a smelter town and a non-lead-exposed town in Yugoslavia were followed up prospectively from pregnancy through age 3. The Child Behavior Checklist was used to assess behavior problems in 379 3-year-olds, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(72 citation statements)
references
References 31 publications
2
69
0
1
Order By: Relevance
“…The eventual result of this cycle might be child behavior that is sufficient to meet criteria for ADHD, conduct disorder, or some other diagnosis. This is relevant to lead studies because increased exposure has been associated with less optimal behavior in very young children (Sciarillo et al, 1992;Wasserman et al, 1998) and with increased aggression, oppositional behaviors, and juvenile delinquency in older children (Needleman et al, 1996;Needleman et al, 2002). What happens to the developmental environment as a lead-exposed child ages has largely been ignored, specifically the possibility that parenting behaviors changed over time, at least in part, as a result of a child's early lead exposure.…”
Section: Conceptual and Analytical Issues Germane To The Role Of Ses mentioning
confidence: 99%
“…The eventual result of this cycle might be child behavior that is sufficient to meet criteria for ADHD, conduct disorder, or some other diagnosis. This is relevant to lead studies because increased exposure has been associated with less optimal behavior in very young children (Sciarillo et al, 1992;Wasserman et al, 1998) and with increased aggression, oppositional behaviors, and juvenile delinquency in older children (Needleman et al, 1996;Needleman et al, 2002). What happens to the developmental environment as a lead-exposed child ages has largely been ignored, specifically the possibility that parenting behaviors changed over time, at least in part, as a result of a child's early lead exposure.…”
Section: Conceptual and Analytical Issues Germane To The Role Of Ses mentioning
confidence: 99%
“…Our data indicate that prenatal and childhood exposure to environmental Pb is associated with a wide range of health outcomes, induding decrements in intelligence (14,20,30), increases in blood pressure (21), higher risks of proteinuria, increases in behavior problems (40), and perturbed hematopoiesis .…”
Section: Discussionmentioning
confidence: 89%
“…In both towns combined, PbB measured concurrently with the Child Behavior Checklist was associated with small increases in behavioral problems, which the authors considered small compared with the effects of social factors (Wasserman et al 1998). In a subsequent publication, Wasserman et al (2000a) observed that while postnatal elevations that occurred before the age of 2 years and continued afterwards were associated with the largest decrements in IQ (50% increase in postnatal lead associated with 2.71 point IQ loss), elevations in PbB that occurred only after the age of 2 years were also associated with decrements.…”
Section: Health Effectsmentioning
confidence: 99%